Delineation of Coal Identification Using Inversion Microtremor and Borehole at PT X - Rahmawati, Nurul Ilmi; Refrizon, Refrizon; Kusuma, Budi Praba; Ansory, Andre Rahmat Al; Syah, M. Taufiqqurahman; Anggria, Della Cici; Triutami, Olga (Talenta Publisher, 2024)
Coal is a natural resource composed of organic and inorganic materials. The potential of coal is one of the national and world resources. Microtremor method is a geophysical exploration method that utilises microseismic waves to identify the presence of hydrocarbons. Microtremor data processing is processed first using Geopsy software to obtain the H/V curve which will then be processed using Hv-Inv software to obtain the Vs value. Microtremor data is correlated with data from the borehole, the coal seam thickens to the southwest. Similarly, with the correlation results of other microtremor cross sections, the cross section shows that the coal seam is thickened and continuous to the west or southwest. This is further strengthened by the existence of boreholes as a correlation of coal Vs value data in the range of 613.37 m/s-887.70 m/s. Other constituent materials such as soil,claystone, sandstone, carboneseus. Based on the Vs value of the 1D model, it is known that the research area shows the distribution of coal at a depth of 53.5-76 metres. The coal layer in the study area is bituminous to sub-bituminous coal.